Pain Identifies Squamous Cell Carcinoma in Organ Transplant Recipients: The SCOPE‐ITSCC PAIN Study. Issue 3 (24th January 2014) - Bouwes Bavinck, J. N.; Harwood, C. A.; Genders, R. E.; Wisgerhof, H. C.; Plasmeijer, E. I.; Mitchell, L.; Olasz, E. B.; Mosel, D. D.; Pokorney, M. S.; Serra, A. L.; Feldmeyer, L.; Baumann Conzett, K.; et al.
<x xml:space="preserve">Abstract</x> Organ transplant recipients (OTR) are at high risk for cutaneous squamous cell carcinomas (SCC). We aimed to define clinically meaningful patient‐reported warning signals predicting the presence of invasive SCC. Patient‐reported signs and symptoms of 812 consecutively biopsied skin lesions from 410 OTR were determined by questionnaire and physical examination and related to the subsequent biopsy‐proven diagnoses. Receiver‐operating characteristic (ROC) curve analyses were used as a measure of distinction between the predictive values of patient‐reported warning signals and the occurrence of SCC. Pain was an independent predictive patient‐reported warning signal for a biopsy‐proven invasive SCC. The odds ratio from the fully adjusted model predicting SCC was 4.4 (95% confidence interval: 2.4–8.2). Higher scores on the visual analog scale (VAS) for pain were associated with a greater likelihood for the presence of SCC compared to none or mild pain. The for scores on the VAS from 1 to 3, 4 to 6 and 7 to 10 were 4.9 (2.2–10.5), 2.3 (0.96–5.5) and 16.5 (3.6–75.8), respectively. Pain is the most powerful patient‐reported warning signal for invasive cutaneous SCC in OTR. Empowerment of patients by education could accelerate diagnosis and treatment of cutaneous SCC.